2020
DOI: 10.1016/j.parkreldis.2019.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted salience network dynamics in Parkinson's disease patients with impulse control disorders

Abstract: Background: Dynamic functional network analysis may add relevant information about the temporal nature of the neurocognitive alterations in PD patients with impulse control disorders (PD-ICD). Our aim was to investigate changes in dynamic functional network connectivity (dFNC) in PD-ICD patients, and topological properties of such networks. Methods: Resting state fMRI was performed on 16 PD PD-ICD patients, 20 PD patients without ICD and 17 healthy controls, whose demographic, clinical and behavioral scores we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 30 publications
2
29
0
Order By: Relevance
“…In contrast, increased morphological connections were observed in PD mainly involving the frontoparietal and salience network, which subserve cognitive and executive functions (Menon 2011). Our findings are consistent with numerous studies showing greater activation (Caminiti et al 2015;Marie et al 2007), and increased centrality (Zhang et al 2015b) and functional connectivity (de Schipper et al 2018;Navalpotro-Gomez et al 2020) in PD. These increases may perhaps reflect cerebral compensation for primary pathophysiological changes.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, increased morphological connections were observed in PD mainly involving the frontoparietal and salience network, which subserve cognitive and executive functions (Menon 2011). Our findings are consistent with numerous studies showing greater activation (Caminiti et al 2015;Marie et al 2007), and increased centrality (Zhang et al 2015b) and functional connectivity (de Schipper et al 2018;Navalpotro-Gomez et al 2020) in PD. These increases may perhaps reflect cerebral compensation for primary pathophysiological changes.…”
Section: Discussionsupporting
confidence: 91%
“…In the single study that examined dynamic functional connectivity over time, ICB+ vs ICB-were found to be engaged for longer in a brain configuration pattern characterized by strong 'within' network connections between superior temporal lobe, fronto-insular and cingulate cortices, at the expense of connectivity with other networks. The same study also reported increased local efficiency within the superior temporal lobe, fronto-insular and cingulate cortices [36].…”
Section: Resting-state Fmri Studiesmentioning
confidence: 69%
“…Of the included 30 papers, 12 evaluated structural alterations [13][14][15][16][17][18][19][20][21][22][23][24], 12 evaluated functional alterations [25][26][27][28][29][30][31][32][33][34][35][36], and 6 included both structural and functional measures [37][38][39][40][41][42]. The study of Hammes et al [18] was included in the structural section only, as no between groups analysis was done in functional alteration analysis.…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tahmasian et al reported aberrant FC in bilateral inferior parietal lobule and the supramarginal gyrus in PD patients and found that these regions formed an interconnected network in PD patients, mainly with the DMN (Tahmasian et al., 2017). In another article, functional connections of the SN increase in group comparisons PD and HC (Navalpotro‐Gomez et al., 2020). Tessitore's et al also examined the salience, central executive, and DMN and showed that there was an increase in connectivity in the SN and DMN, as well as reduced connectivity in the central executive networks (Tessitore et al., 2017).…”
Section: Introductionmentioning
confidence: 98%